Physicochemical Properties, Antioxidant Activity, and Flavor Profile of Strawberry Fruit-Based Novel Drinking Jelly Made with Gracilaria fisheri Seaweed as a Gelling Agent at Varying Concentrations - Narin Charoenphun; Paramee Noonim; Somwang Lekjing; Chawakwan Nitikornwarakul; Nam Hoang Pham; Karthikeyan Venkatachalam (Gels)
Gracilaria fisheri (GF) is a red seaweed that is widely found in Southeast Asia and has gained attention for its potential bioactive compounds and versatile applications in food products. This study explored the potential of GF as a natural gelling agent in the development of sustainable strawberry-based drinking jelly. By utilizing GF at varying concentrations (0.2 (S1), 0.4 (S2), 0.6 (S3), 0.8 (S4), and 1.0% (S5)), the impact on the physicochemical, textural, phytochemical, and flavor profiles of the strawberry concentrate-based drinking jelly was examined. The results demonstrated that GF concentration significantly affected the color characteristics, structural development, and flavor profiles of the drinking jelly samples. Increasing GF levels progressively enhanced the lightness (L*) and redness (a*) values while reducing the yellowness (b*), with optimal visual appeal achieved in the S4 samples compared to others. Microscopical observations revealed that gel matrix development improved with GF concentrations up to 0.8% (S4), transitioning from a sparse, liquid-like structure at lower levels to a compact, over-gelated network at 1.0% (S5). Physicochemical parameters, including pH, total soluble solid (TSS), and TSS/titratable acidity (TA) ratios, increased with GF levels, contributing to a sweeter, less acidic product, while water activity (aw) decreased, enhancing jelly stability. Viscosity and sulfate content increased significantly with GF concentration, indicating improved gel strength but reduced fluidity. Phytochemical analysis revealed that ascorbic acid (AsA) and total phenolic content (TPC) decreased progressively with higher GF levels, leading to a reduction in antioxidant activity (DPPH and ABTS). Volatile compound analysis identified alcohols, esters, and aldehydes as dominant contributors to the flavor profile. 1-Octanol (waxy, citrus-like) and methyl anthranilate (grape-like, sweet) increased substantially, while minor groups such as terpenoids and phenolic compounds contributed floral and woody notes. The findings suggest that S4 samples strike the optimal balance between texture, color, flavor, and antioxidant properties, achieving a cohesive, visually appealing, and flavorful drinking jelly suitable for commercial applications.